Inclusion complexes of cysteinyl β‐cyclodextrin with baicalein restore collagen synthesis in fibroblast cells following ultraviolet exposure. Issue 3 (30th September 2018) - Lee, Joomin; Ahn, Eunsook; Kim, Seon‐Y.; Shin, Yujeong; Ahn, Seunghyun; Sung, Jiha; Kim, Hwanhee; Cho, Eunae; Jung, Seunho; Park, Seyeon
Abstract: Baicalein, a bioactive flavonoid, has poor water solubility, thereby limiting its use in a wide range of biological applications. In the present study, we used inclusion complexes of cysteinyl β‐cyclodextrin (β‐CD) with baicalein to enhance the stability and solubility of baicalein in aqueous solution. We examined the effects of inclusion complexes of cysteinyl β‐CD on collagen synthesis following ultraviolet (UV) irradiation, as well as the mechanisms underlying its effects. Our findings demonstrated that baicalein significantly restored collagen synthesis in the UV‐exposed human fibroblast Hs68 cells. In addition, synthetic cysteine functionalized β‐CDs were found to promote baicalein‐induced collagen synthesis. Inclusion complexes of cysteinyl β‐CDs with baicalein significantly upregulated the protein expression of type I collagen and activated the transcription of type I, II, and III collagen. Inclusion complexes of cysteinyl β‐CDs with baicalein also downregulated matrix metalloproteinase ‐1 and ‐3, and α‐smooth muscle actin expression. In addition, inclusion complexes of cysteinyl β‐CDs with baicalein attenuated the expression of caveolin‐1, but this treatment enhanced the UV‐induced phosphorylation of Smad in the transforming growth factor‐β pathway. These results suggested that the newly synthesized derivative of CD can be used as a complexing agent to enhance the bioavailability of flavonoids such as baicalein, especially in restoring collagen synthesis. Abstract : We show that newly synthesized derivative of cysteinyl β‐cyclodextrin can be used as complexing agent to enhance the bioavailability of flavonoids such as baicalein, especially in restoring collagen synthesis in ultraviolet‐exposed human fibroblast Hs68 cells.